Resin compositions, prepregs, resin-coated films, resin-coated metal foils, metal-clad laminates, and wiring boards

JP7943554B2Active Publication Date: 2026-10-30PANASONIC INTELLECTUAL PROPERTY MANAGEMENT CO LTD
View PDF 12 Cites 0 Cited by

Patent Information

Application Number
JP2023569086
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2021-12-24
Filing Date
2022-10-13
Publication Date
2026-10-30
Estimated Expiration
2042-10-13

Smart Images

  • Figure 0007943554000020
    Figure 0007943554000020
  • Figure 0007943554000021
    Figure 0007943554000021
  • Figure 0007943554000022
    Figure 0007943554000022
Patent Text Reader

Abstract

One aspect of the present invention relates to a resin composition which contains a poly(phenylene ether) compound (A), a curing agent (B), an inorganic filler (C) containing boron nitride, and a phosphorus compound (D). In a particle size distribution of the inorganic filler (C), at least two peaks are present within a particle size range of 1.0-50.0 µm in a particle size distribution measured using a laser diffraction type particle size distribution measurement method. The phosphorus compound (D) contains: a compatible phosphorus compound (D-1) that is compatible with a mixture of the poly(phenylene ether) compound (A) and the curing agent (B); and an incompatible phosphorus compound (D-2) that is not compatible with the mixture.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical Field]

[0001] The present invention relates to resin compositions, prepregs, resin-coated films, resin-coated metal foils, metal-clad laminates, and wiring boards. [Background technology]

[0002] As the amount of information processing required for various electronic devices increases, mounting technologies such as the high integration of semiconductor devices, high density of wiring, and multilayering are advancing. Furthermore, the wiring boards used in various electronic devices are required to be high-frequency compatible, such as millimeter-wave radar substrates in automotive applications. In order to increase the signal transmission speed, wiring boards used in various electronic devices are required to reduce signal transmission losses, and this is especially important for high-frequency compatible wiring boards. To meet this requirement, the substrate material that constitutes the base material of the wiring board used in various electronic devices is required to have low dielectric constant and dielectric loss tangent.

[0003] As such a base material, for example, a PPE-containing resin composition containing PPE (polyphenylene ether), a crosslinked curable compound, and a phosphaphenanthrene derivative has been reported to exhibit excellent low dielectric properties and glass transition temperature (Tg) (Patent Document 1).

[0004] On the other hand, electronic materials used in PA (power amplifier) ​​substrates for base stations require not only low dielectric constant and dielectric loss tangent, but also high thermal conductivity. To date, resin compositions for derivatives containing anisotropic magnesium oxide have been reported as one method for improving the thermal conductivity of resin compositions (Patent Document 2), but a technique using boron nitride as an inorganic filler has been reported to obtain even higher thermal conductivity (Patent Document 3 or Patent Document 4).

[0005] The boron nitride fillers described in Patent Documents 3 and 4 above certainly improve the thermal conductivity of resin compositions. However, when using resin compositions as molding materials such as substrate materials, even better flame retardancy is required. In this regard, the resin composition described in Patent Document 1 above contains a phosphaphenanthrene derivative, which is used as a flame retardant, added to a polyphenylene ether resin. Phosphaphenanthrene derivatives are known as halogen-free phosphorus-based flame retardants.

[0006] However, research by the inventors has revealed that using phosphorus-based flame retardants that are compatible with resins, or phosphorus-based flame retardants that are not compatible with resins, individually, degrades thermal conductivity and Tg. [Prior art documents] [Patent Documents]

[0007] [Patent Document 1] Japanese Patent Publication No. 2015-67700 [Patent Document 2] Japanese Patent Publication No. 2015-168731 [Patent Document 3] Japanese Patent Publication No. 2013-241321 [Patent Document 4] Japanese Patent Publication No. 2014-208818 [Overview of the Initiative]

[0008] The present invention has been made in view of the above circumstances, and aims to provide a resin composition that can produce a cured product with low dielectric properties, high thermal conductivity and glass transition temperature (Tg), and excellent flame retardancy. The present invention also aims to provide a prepreg, a resin-coated film, a resin-coated metal foil, a metal-clad laminate, and a wiring board that can be obtained using the above resin composition.

[0009] After various studies, the inventors found that the above objective could be achieved by the following configuration, and through further investigation, they achieved the present invention.

[0010] That is, the resin composition according to one aspect of the present invention comprises a polyphenylene ether compound (A), a curing agent (B), an inorganic filler (C) containing boron nitride, and a phosphorus compound (D). In the particle size distribution of the inorganic filler (C), at least two peaks of the particle size distribution measured by a laser diffraction particle size distribution measurement method exist in the particle size range of 1.0 to 50.0 μm, and the phosphorus compound (D) contains a compatible phosphorus compound (D-1) that is compatible with the mixture of the polyphenylene ether compound (A) and the curing agent (B), and an incompatible phosphorus compound (D-2) that is incompatible with the aforementioned mixture. [Brief Description of Drawings]

[0011] [Figure 1] FIG. 1 is a schematic cross-sectional view showing an example of the prepreg according to the embodiment of the present invention. [Figure 2] FIG. 2 is a schematic cross-sectional view showing an example of the metal-clad laminate according to the embodiment of the present invention. [Figure 3] FIG. 3 is a schematic cross-sectional view showing an example of the wiring board according to the embodiment of the present invention. [Figure 4] FIG. 4 is a schematic cross-sectional view showing an example of the resin-attached metal foil according to the embodiment of the present invention. [Figure 5] FIG. 5 is a schematic cross-sectional view showing an example of the resin-attached film according to the embodiment of the present invention. [Mode for Carrying Out the Invention]

[0012] Hereinafter, the embodiments according to the present invention will be specifically described, but the present invention is not limited thereto.

[0013] [Resin Composition] A resin composition according to an embodiment of the present invention comprises a polyphenylene ether compound (A), a curing agent (B), an inorganic filler (C) containing boron nitride, and a phosphorus compound (D), wherein the particle size distribution of the inorganic filler (C) has at least two peaks in the particle size distribution measured by laser diffraction particle size distribution measurement method in the particle size range of 1.0 to 50.0 μm, and the phosphorus compound (D) contains a miscible phosphorus compound (D-1) that is miscible with the mixture of the polyphenylene ether compound (A) and the curing agent (B), and an inmiscible phosphorus compound (D-2) that is not miscible with the mixture of the polyphenylene ether compound (A) and the curing agent (B).

[0014] With the above configuration, a resin composition can be obtained that yields a cured product with low dielectric properties (relative permittivity), high thermal conductivity and Tg, and excellent adhesion and flame retardancy. Furthermore, according to the present invention, by using the above resin composition, it is possible to provide prepregs, resin-coated films, resin-coated metal foils, metal-clad laminates, and wiring boards with excellent performance.

[0015] First, let's describe each component of the resin composition of this embodiment.

[0016] (Polyphenylene ether compound (A)) The polyphenylene ether compound (A) in this embodiment is not particularly limited, but from the viewpoint of lowering dielectric properties, it is preferable to be a modified polyphenylene ether compound. More preferably, it is a modified polyphenylene ether compound (A-1) having a group represented by formula (1) or formula (2) described later. It is believed that by including such a polyphenylene ether compound, a resin composition can be obtained in which a cured product with low dielectric properties and high heat resistance can be obtained.

[0017] [ka]

[0018] In formula (1), s represents an integer from 0 to 10. Z represents an arylene group. R1 to R3 are independent of each other; that is, R1 to R3 may be the same group or different groups. R1 to R3 represent a hydrogen atom or an alkyl group.

[0019] In equation (1), if s is 0, it indicates that Z is directly bonded to the end of the polyphenylene ether.

[0020] The arylene group Z described above is not particularly limited. Examples of this arylene group include monocyclic aromatic groups such as phenylene groups, and polycyclic aromatic groups in which the aromatic element is not monocyclic but polycyclic, such as naphthalene rings. Furthermore, this arylene group also includes derivatives in which the hydrogen atom bonded to the aromatic ring is substituted with a functional group such as an alkenyl group, alkynyl group, formyl group, alkylcarbonyl group, alkenylcarbonyl group, or alkynylcarbonyl group. The alkyl group is not particularly limited, for example, alkyl groups having 1 to 18 carbon atoms are preferred, and alkyl groups having 1 to 10 carbon atoms are more preferred. Specifically, examples include methyl groups, ethyl groups, propyl groups, hexyl groups, and decyl groups.

[0021] [ka]

[0022] In formula (2), R4 represents a hydrogen atom or an alkyl group. The alkyl group is not particularly limited, but for example, alkyl groups having 1 to 18 carbon atoms are preferred, and alkyl groups having 1 to 10 carbon atoms are more preferred. Specifically, examples include methyl groups, ethyl groups, propyl groups, hexyl groups, and decyl groups.

[0023] Preferred specific examples of substituents represented by formula (1) include substituents containing a vinylbenzyl group. Examples of substituents containing a vinylbenzyl group include substituents represented by the following formula (6). Examples of substituents represented by formula (2) include acrylate groups and methacrylate groups.

[0024] [ka]

[0025] More specifically, examples of the substituents include vinyl benzyl groups (ethenyl benzyl groups) such as p-ethenylbenzyl groups and m-ethenylbenzyl groups, vinylphenyl groups, acrylate groups, and methacrylate groups.

[0026] The polyphenylene ether compound has a polyphenylene ether chain in its molecule, and preferably has a repeating unit represented by the following formula (7) in its molecule.

[0027] [ka]

[0028] In formula (7), t represents a value between 1 and 50. Furthermore, R5 to R8 are independent of each other. That is, R5 to R8 may be the same group or different groups. Also, R5 to R8 represent a hydrogen atom, an alkyl group, an alkenyl group, an alkynyl group, a formyl group, an alkylcarbonyl group, an alkenylcarbonyl group, or an alkynylcarbonyl group. Among these, hydrogen atoms and alkyl groups are preferred.

[0029] In R5 to R8, the functional groups listed are specifically as follows:

[0030] The alkyl group is not particularly limited, but for example, alkyl groups having 1 to 18 carbon atoms are preferred, and alkyl groups having 1 to 10 carbon atoms are more preferred. Specifically, examples include methyl groups, ethyl groups, propyl groups, hexyl groups, and decyl groups.

[0031] The alkenyl group is not particularly limited, but for example, an alkenyl group having 2 to 18 carbon atoms is preferred, and an alkenyl group having 2 to 10 carbon atoms is more preferred. Specifically, examples include vinyl groups, allyl groups, and 3-butenyl groups.

[0032] The alkynyl group is not particularly limited, but for example, an alkynyl group having 2 to 18 carbon atoms is preferred, and an alkynyl group having 2 to 10 carbon atoms is more preferred. Specifically, examples include the ethynyl group and the propa-2-in-1-yl group (propargyl group).

[0033] The alkylcarbonyl group is not particularly limited as long as it is a carbonyl group substituted with an alkyl group, but for example, alkylcarbonyl groups having 2 to 18 carbon atoms are preferred, and alkylcarbonyl groups having 2 to 10 carbon atoms are more preferred. Specifically, examples include acetyl group, propionyl group, butyryl group, isobutyryl group, pivaloyl group, hexanoyl group, octanoyl group, and cyclohexylcarbonyl group.

[0034] The alkenylcarbonyl group is not particularly limited as long as it is a carbonyl group substituted with an alkenyl group, but for example, an alkenylcarbonyl group having 3 to 18 carbon atoms is preferred, and an alkenylcarbonyl group having 3 to 10 carbon atoms is more preferred. Specifically, examples include acryloyl groups, methacryloyl groups, and crotonoyl groups.

[0035] The alkynylcarbonyl group is not particularly limited as long as it is a carbonyl group substituted with an alkynyl group, but for example, an alkynylcarbonyl group having 3 to 18 carbon atoms is preferred, and an alkynylcarbonyl group having 3 to 10 carbon atoms is more preferred. Specifically, for example, a propioloyl group can be mentioned.

[0036] The weight-average molecular weight (Mw) of the polyphenylene ether compound is not particularly limited. Specifically, it is preferably 500 to 5000, more preferably 800 to 4000, and even more preferably 1000 to 3000. Here, the weight-average molecular weight can be measured by any general molecular weight measurement method, specifically, values ​​measured using gel permeation chromatography (GPC). Furthermore, if the polyphenylene ether compound has repeating units represented by formula (11) in its molecule, it is preferable that t is a value such that the weight-average molecular weight of the polyphenylene ether compound falls within this range. Specifically, it is preferable that t is 1 to 50.

[0037] When the weight-average molecular weight of the polyphenylene ether compound is within this range, it possesses the excellent low dielectric properties of polyphenylene ether, resulting in a cured product that is not only superior in heat resistance but also in moldability. This is thought to be due to the following: In ordinary polyphenylene ethers, when the weight-average molecular weight is within this range, the molecular weight is relatively low, so the heat resistance of the cured product tends to decrease. In this respect, the polyphenylene ether compound according to this embodiment has one or more unsaturated double bonds at its terminals, so it is thought that a cured product with sufficiently high heat resistance can be obtained. Furthermore, when the weight-average molecular weight of the polyphenylene ether compound is within this range, the molecular weight is relatively low, so it is thought to have excellent moldability. Therefore, it is thought that such a polyphenylene ether compound can be obtained that is not only superior in heat resistance but also in moldability.

[0038] The average number of substituents (terminal functional groups) at the molecular ends of each molecule of the polyphenylene ether compound is not particularly limited. Specifically, it is preferably 1 to 5, more preferably 1 to 3, and even more preferably 1.5 to 3. If the number of terminal functional groups is too small, it tends to be difficult to obtain a cured product with sufficient heat resistance. On the other hand, if the number of terminal functional groups is too large, the reactivity becomes too high, which may lead to problems such as a decrease in the shelf life of the resin composition or a decrease in the fluidity of the resin composition. In other words, using such a polyphenylene ether compound may result in molding defects such as voids occurring during multilayer molding due to insufficient fluidity, making it difficult to obtain a highly reliable printed circuit board.

[0039] The number of terminal functional groups in a polyphenylene ether compound can be expressed as a numerical value representing the average number of substituents per molecule of the modified polyphenylene ether compound present in 1 mole of the polyphenylene ether compound. This number of terminal functional groups can be measured, for example, by measuring the number of hydroxyl groups remaining in the obtained modified polyphenylene ether compound and calculating the decrease from the number of hydroxyl groups in the polyphenylene ether before modification. This decrease from the number of hydroxyl groups in the polyphenylene ether before modification is the number of terminal functional groups. The number of hydroxyl groups remaining in the modified polyphenylene ether compound can be measured by adding a quaternary ammonium salt (tetraethylammonium hydroxide) that associates with hydroxyl groups to a solution of the modified polyphenylene ether compound and measuring the UV absorbance of the resulting mixed solution.

[0040] The intrinsic viscosity of the polyphenylene ether compound (A) in this embodiment is not particularly limited. Specifically, it may be 0.03 to 0.12 dl / g, but preferably 0.04 to 0.11 dl / g, and more preferably 0.06 to 0.095 dl / g. If the intrinsic viscosity is too low, the molecular weight tends to be low, and it tends to be difficult to obtain low dielectric properties such as low dielectric constant and low dielectric loss tangent. On the other hand, if the intrinsic viscosity is too high, the viscosity is high, sufficient fluidity cannot be obtained, and the moldability of the cured product tends to decrease. Therefore, if the intrinsic viscosity of the polyphenylene ether compound is within the above range, excellent heat resistance and moldability of the cured product can be achieved.

[0041] The intrinsic viscosity referred to here is the intrinsic viscosity measured in methylene chloride at 25°C. More specifically, it is the value measured using a viscometer in a 0.18 g / 45 ml methylene chloride solution (at a liquid temperature of 25°C). Examples of such viscometers include the Schott AVS500 Visco System.

[0042] Examples of the polyphenylene ether compound (A) in this embodiment include a modified polyphenylene ether compound represented by the following formula (8) and a modified polyphenylene ether compound represented by the following formula (9). Furthermore, these modified polyphenylene ether compounds may be used individually or in combination as the polyphenylene ether compound in this embodiment.

[0043] [ka]

[0044] [ka]

[0045] In equations (8) and (9), R9~R 16 R 17 ~R 24each independently represents a hydrogen atom, an alkyl group, an alkenyl group, an alkynyl group, a formyl group, an alkylcarbonyl group, an alkenylcarbonyl group, or an alkynylcarbonyl group. X1 and X2 each independently represent a substituent having a carbon-carbon unsaturated double bond. A and B represent the repeating units represented by the following formula (10) and the following formula (11), respectively. Further, in formula (9), Y represents a linear, branched, or cyclic hydrocarbon having 20 or less carbon atoms.

[0046]

Chemical Formula

[0047]

Chemical Formula

[0048] In formula (10) and formula (11), m and n each represent 0 to 20. R 25 to R 28 and R 29 to R 32 each independently represents a hydrogen atom, an alkyl group, an alkenyl group, an alkynyl group, a formyl group, an alkylcarbonyl group, an alkenylcarbonyl group, or an alkynylcarbonyl group.

[0049] The modified polyphenylene ether compound represented by the above formula (8) and the modified polyphenylene ether compound represented by the above formula (9) are not particularly limited as long as they are compounds satisfying the above configuration. Specifically, in the above formula (8) and the above formula (9), R9 to R 16 and R 17 to R 24 are each independent as described above. That is, R9 to R 16 and R 17 to R 24 may each be the same group or different groups. Further, R9 to R 16 and R 17 to R 24This represents a hydrogen atom, an alkyl group, an alkenyl group, an alkynyl group, a formyl group, an alkylcarbonyl group, an alkenylcarbonyl group, or an alkynylcarbonyl group. Among these, hydrogen atoms and alkyl groups are preferred.

[0050] In equations (10) and (11), it is preferable that m and n represent values ​​between 0 and 20, as described above. Furthermore, it is preferable that m and n represent values ​​such that the sum of m and n is between 1 and 30. Therefore, it is more preferable that m represents values ​​between 0 and 20, n represents values ​​between 0 and 20, and the sum of m and n is between 1 and 30. Also, R 25 ~R 28 R 29 ~R 32 They are independent of each other. That is, R 25 ~R 28 R 29 ~R 32 These may be the same group or different groups. Also, R 25 ~R 28 R 29 ~R 32 This represents a hydrogen atom, an alkyl group, an alkenyl group, an alkynyl group, a formyl group, an alkylcarbonyl group, an alkenylcarbonyl group, or an alkynylcarbonyl group. Among these, hydrogen atoms and alkyl groups are preferred.

[0051] R9~R 32 This is the same as R5 to R8 in equation (7) above.

[0052] In formula (9) above, Y is a linear, branched, or cyclic hydrocarbon having 20 or fewer carbon atoms, as described above. Examples of Y include the group represented by the following formula (12).

[0053] [ka]

[0054] In the above equation (12), R 33 and R 34Each of these independently represents either a hydrogen atom or an alkyl group. Examples of the alkyl group include a methyl group. Examples of the group represented by formula (12) include a methylene group, a methylmethylene group, and a dimethylmethylene group, among which the dimethylmethylene group is preferred.

[0055] In formulas (8) and (9), X1 and X2 are each independent substituents having a carbon-carbon unsaturated double bond. The substituents X1 and X2 are not particularly limited as long as they have a carbon-carbon unsaturated double bond. Examples of substituents X1 and X2 include the substituent represented by formula (1) and the substituent represented by formula (2). In the modified polyphenylene ether compound represented by formula (8) and the modified polyphenylene ether compound represented by formula (9), X1 and X2 may be the same substituent or different substituents.

[0056] More specific examples of the modified polyphenylene ether compound represented by formula (8) include, for example, the modified polyphenylene ether compound represented by the following formula (13).

[0057] [ka]

[0058] More specific examples of the modified polyphenylene ether compound represented by formula (9) include, for example, the modified polyphenylene ether compound represented by formula (14) below, and the modified polyphenylene ether compound represented by formula (15) below.

[0059] [ka]

[0060] [ka]

[0061] In equations (13) to (15) above, m and n are the same as m and n in equations (10) and (11) above. Also, in equations (13) and (14) above, R1 to R3, p and Z are the same as R1 to R3, s and Z in equation (1) above, respectively. Also, in equations (14) and (15) above, Y is the same as Y in (9) above. Also, in equation (14) above, R4 is the same as R4 in equation (2) above.

[0062] By using the modified polyphenylene ether compounds described above, it is possible to improve high Tg and adhesion while maintaining low dielectric properties such as low dielectric constant and excellent heat resistance.

[0063] Furthermore, modified polyphenylene ether compounds can be used individually or in combination of two or more types.

[0064] The polyphenylene ether compound (A) used in the resin composition of this embodiment can be synthesized by known methods or a commercially available product can be used. Examples of commercially available products include "OPE-2st 1200" and "OPE-2st 2200" from Mitsubishi Gas Chemical Company, Inc., and "SA9000" from SABIC Innovative Plastics Corporation.

[0065] (Hardening agent (B)) The resin composition of this embodiment further comprises a curing agent (B).

[0066] The curing agent (B) is not particularly limited as long as it is a curing agent that can react with the polyphenylene ether compound (A) to cure the resin composition containing the polyphenylene ether compound (A). Examples of curing agents include those having at least one functional group in the molecule that contributes to the reaction with the polyphenylene ether compound (A).

[0067] Specifically, examples include compounds having an acryloyl group in the molecule, compounds having a methacryloyl group in the molecule, compounds having a vinyl group in the molecule, compounds having an allyl group in the molecule, compounds having a maleimide group in the molecule, compounds having an acenaphthylene structure in the molecule, and isocyanurate compounds having an isocyanurate group in the molecule, styrene derivatives, and so on.

[0068] The compound having an acryloyl group in its molecule is an acrylate compound. Examples of acrylate compounds include monofunctional acrylate compounds having one acryloyl group in their molecule, and polyfunctional acrylate compounds having two or more acryloyl groups in their molecule. Examples of monofunctional acrylate compounds include methyl acrylate, ethyl acrylate, propyl acrylate, and butyl acrylate. Examples of polyfunctional acrylate compounds include tricyclodecanedimethanol diacrylate.

[0069] A compound having a methacryloyl group in its molecule is a methacrylate compound. Examples of methacrylate compounds include monofunctional methacrylate compounds having one methacryloyl group in their molecule, and polyfunctional methacrylate compounds having two or more methacryloyl groups in their molecule. Examples of monofunctional methacrylate compounds include methyl methacrylate, ethyl methacrylate, propyl methacrylate, and butyl methacrylate. Examples of polyfunctional methacrylate compounds include tricyclodecanedimethanol dimethacrylate.

[0070] A compound having a vinyl group in its molecule is a vinyl compound. Examples of vinyl compounds include monofunctional vinyl compounds (monovinyl compounds) having one vinyl group in their molecule, and polyfunctional vinyl compounds having two or more vinyl groups in their molecule. Examples of polyfunctional vinyl compounds include divinylbenzene and polybutadiene.

[0071] A compound having an allyl group in its molecule is an allyl compound. Examples of allyl compounds include monofunctional allyl compounds having one allyl group in their molecule, and polyfunctional allyl compounds having two or more allyl groups in their molecule. Examples of polyfunctional allyl compounds include diallyl phthalate (DAP).

[0072] A compound having a maleimide group in its molecule is a maleimide compound. Examples of the maleimide compound include a monofunctional maleimide compound having one maleimide group in its molecule, a polyfunctional maleimide compound having two or more maleimide groups in its molecule, and a modified maleimide compound. Examples of the modified maleimide compound include a modified maleimide compound in which part of the molecule is modified with an amine compound, a modified maleimide compound in which part of the molecule is modified with a silicone compound, and a modified maleimide compound in which part of the molecule is modified with both an amine compound and a silicone compound.

[0073] A compound having an acenaphthylene structure in the molecule is an acenaphthylene compound. Examples of the acenaphthylene compound include acenaphthylene, alkylacenaphthylenes, halogenated acenaphthylenes, and phenylacenaphthylenes. Examples of the alkylacenaphthylenes include 1-methylacenaphthylene, 3-methylacenaphthylene, 4-methylacenaphthylene, 5-methylacenaphthylene, 1-ethylacenaphthylene, 3-ethylacenaphthylene, 4-ethylacenaphthylene, and 5-ethylacenaphthylene. Examples of the halogenated acenaphthylenes include 1-chloroacenaphthylene, 3-chloroacenaphthylene, 4-chloroacenaphthylene, 5-chloroacenaphthylene, 1-bromoacenaphthylene, 3-bromoacenaphthylene, 4-bromoacenaphthylene, and 5-bromoacenaphthylene. Examples of the phenylacenaphthylenes include 1-phenylacenaphthylene, 3-phenylacenaphthylene, 4-phenylacenaphthylene, and 5-phenylacenaphthylene. The acenaphthylene compound may be a monofunctional acenaphthylene compound having one acenaphthylene structure in the molecule, as described above, or a polyfunctional acenaphthylene compound having two or more acenaphthylene structures in the molecule.

[0074] A compound having an isocyanurate group in its molecule is an isocyanurate compound. Examples of isocyanurate compounds include compounds further having an alkenyl group in their molecule (alkenyl isocyanurate compounds), such as triallyl isocyanurate (TAIC) and other triallyl isocyanurate compounds.

[0075] Examples of the styrene derivatives include bromostyrene and dibromostyrene.

[0076] The curing agent (B) used in this embodiment preferably contains at least one selected from the above, for example, a polyfunctional acrylate compound having two or more acryloyl groups in its molecule, a polyfunctional methacrylate compound having two or more methacryloyl groups in its molecule, a polyfunctional vinyl compound having two or more vinyl groups in its molecule, a styrene derivative, an allyl compound having an allyl group in its molecule, a maleimide compound having a maleimide group in its molecule, an acenaphthylene compound having an acenaphthylene structure in its molecule, and an isocyanurate compound having an isocyanurate group in its molecule.

[0077] The curing agent (B) may be one of the curing agents described above, or two or more may be used in combination.

[0078] The curing agent (B) preferably has a weight-average molecular weight of 100 to 5000, more preferably 100 to 4000, and even more preferably 100 to 3000. If the weight-average molecular weight of the curing agent is too low, it may be prone to volatilizing from the resin composition's compound system. Conversely, if the weight-average molecular weight of the curing agent is too high, the viscosity of the varnish of the resin composition and the melt viscosity during heat molding may become too high. Therefore, when the weight-average molecular weight of the curing agent is within this range, a resin composition with superior heat resistance of the cured product can be obtained. This is thought to be because the reaction with the polyphenylene ether compound allows for suitable curing of the resin composition containing the polyphenylene ether compound. Here, the weight-average molecular weight can be any value measured by a general molecular weight measurement method, specifically, values ​​measured using gel permeation chromatography (GPC).

[0079] The curing agent (B) has an average number of functional groups per molecule that contribute to the reaction with the polyphenylene ether compound. The number of functional groups varies depending on the weight-average molecular weight of the curing agent, but is preferably 1 to 20, and more preferably 2 to 18. If the number of functional groups is too small, it tends to be difficult to obtain a cured product with sufficient heat resistance. On the other hand, if the number of functional groups is too large, the reactivity becomes too high, which may lead to problems such as a decrease in the shelf life of the resin composition or a decrease in the fluidity of the resin composition.

[0080] (Inorganic filler (C)) The resin composition according to this embodiment further comprises an inorganic filler (C) containing boron nitride. The boron nitride can be used as an inorganic filler contained in the resin composition and is not particularly limited as long as it satisfies the particle size distribution requirements described later. Examples of boron nitride include the hexagonal atmospheric pressure phase (h-BN) and the cubic high-pressure phase (c-BN).

[0081] In the inorganic filler (C) of this embodiment, the particle size distribution of the inorganic filler has at least two peaks in the particle size distribution measured by laser diffraction particle size distribution measurement method, within the particle size range of 1.0 to 50.0 μm. In other words, the inorganic filler used in this embodiment is a mixture of inorganic fillers having at least two or more peak particle sizes (peak tops). By using an inorganic filler (C) in which at least two peaks are present within the aforementioned particle size range, high thermal conductivity and low dielectric properties (Dk) can be achieved in the cured resin composition.

[0082] Furthermore, it is preferable that each of these peaks has at least one in the particle size range of 1.0 to 5.0 μm and at least one in the particle size range of 5.0 to 50.0 μm. In other words, the inorganic filler used in the more preferred embodiment is a mixture of a relatively small particle size inorganic filler, a relatively large particle size inorganic filler, and an inorganic filler having at least two or more peak particle sizes (peak tops). This is thought to enable both ensuring adhesion to the metal foil and achieving high thermal conductivity. If there is only one peak in the particle size distribution of the inorganic filler, and the peak is only in the small particle size range, the adhesion of the cured resin composition to the metal foil tends not to be sufficiently improved. Also, if the peak is only in the large particle size range, the thermal conductivity of the obtained resin composition tends to decrease.

[0083] In this specification, the particle size distribution is a value measured by the laser diffraction / scattering method, which can be measured using, for example, the laser diffraction / scattering particle size distribution analyzer "LA-960V2" (manufactured by Horiba, Ltd.) used in the examples described later. In this embodiment, the peak refers to the maximum value in the particle size distribution graph, and specifically, it is a numerical value obtained from the maximum value in the particle size distribution graph when the horizontal axis is particle diameter and the vertical axis is relative particle quantity (frequency).

[0084] Furthermore, it is preferable that, with respect to 100 volume percent of the overall particle size distribution of the inorganic filler (C), the cumulative percentage of particles with a particle size in the range of 0.1 to 5.0 μm is 25 to 75 volume percent, and the cumulative percentage of particles with a particle size of 5.0 to 100.0 μm is 25 to 75 volume percent. Each of these cumulative percentages (%) is calculated from the cumulative value of the relative particle amount in each particle size range. This has the advantage of ensuring both adhesion to the copper foil and high thermal conductivity.

[0085] Furthermore, it is preferable that the boron nitride contained in the inorganic filler (C) of this embodiment is identified by energy-dispersive X-ray analysis (EDX analysis) of the vertical cross-sectional view of the cured resin composition of this embodiment, and that in SEM observation, among the boron nitride present within a 50 μm side, there are 3 to 30 boron nitrides whose longest length from end to end is between 10 μm and 50 μm. This has the advantage of ensuring adhesion to copper foil while maintaining high thermal conductivity.

[0086] The resin composition of this embodiment may contain only boron nitride, or it may contain inorganic fillers other than boron nitride. The content of boron nitride in the inorganic filler (C) is preferably 20 to 100 parts by mass, and more preferably 30 to 80 parts by mass, per 100 parts by mass of the inorganic filler (C). It is believed that having a boron nitride content within this range has the advantage of ensuring high thermal conductivity.

[0087] If only boron nitride is included, two or more types of boron nitride with different particle sizes are used so that the particle size distribution of the inorganic filler (C) satisfies the above-mentioned requirements. Furthermore, if inorganic fillers other than boron nitride are included, the particle size of the boron nitride and the particle size of the inorganic fillers other than boron nitride may be adjusted so that the particle size distribution of the inorganic filler (C) satisfies the above-mentioned requirements.

[0088] The inorganic fillers other than boron nitride are not particularly limited, as long as they can be used as inorganic fillers contained in the resin composition. Examples of inorganic fillers other than boron nitride include metal oxides such as silica, alumina, titanium oxide, magnesium oxide and mica, metal hydroxides such as aluminum hydroxide and magnesium hydroxide, talc, aluminum borate, barium sulfate, aluminum nitride, silicon nitride, magnesium carbonate such as anhydrous magnesium carbonate, and calcium carbonate. Among these, silica, anhydrous magnesium carbonate, alumina, and silicon nitride are preferred as inorganic fillers other than boron nitride. The silica is not particularly limited, and examples include crushed silica and silica particles, with silica particles being preferred. The magnesium carbonate is not particularly limited, but anhydrous magnesium carbonate (synthetic magnesite) is preferred.

[0089] The inorganic filler other than boron nitride may be a surface-treated inorganic filler or an untreated inorganic filler. Examples of surface treatments include treatment with a silane coupling agent.

[0090] Examples of the silane coupling agent include silane coupling agents having at least one functional group selected from the group consisting of vinyl group, styryl group, methacryloyl group, acryloyl group, and phenylamino group. Specifically, this silane coupling agent is a compound having at least one of vinyl group, styryl group, methacryloyl group, acryloyl group, and phenylamino group as a reactive functional group, and further having a hydrolyzable group such as a methoxy group or an ethoxy group.

[0091] Examples of silane coupling agents that have a vinyl group include vinyltriethoxysilane and vinyltrimethoxysilane. Examples of silane coupling agents that have a styryl group include p-styryltrimethoxysilane and p-styryltriethoxysilane. Examples of silane coupling agents that have a methacryloyl group include 3-methacryloxypropyltrimethoxysilane, 3-methacryloxypropylmethyldimethoxysilane, 3-methacryloxypropyltriethoxysilane, 3-methacryloxypropylmethyldiethoxysilane, and 3-methacryloxypropylethyldiethoxysilane. Examples of silane coupling agents that have an acryloyl group include 3-acryloxypropyltrimethoxysilane and 3-acryloxypropyltriethoxysilane. Examples of silane coupling agents having a phenylamino group include N-phenyl-3-aminopropyltrimethoxysilane and N-phenyl-3-aminopropyltriethoxysilane.

[0092] Furthermore, if the inorganic filler of this embodiment contains inorganic fillers other than boron nitride, it is preferable that the content of boron nitride in the inorganic filler is 20 to 100 parts by volume per 100 parts by volume of the inorganic filler. This is thought to allow for a more reliable achievement of high thermal conductivity. A more preferable range is 30 to 70 parts by volume.

[0093] In this embodiment, the average particle size of the boron nitride and / or the average particle size of the inorganic filler other than the boron nitride is not particularly limited, as long as the particle size distribution of the inorganic filler (C) satisfies the above-described requirements.

[0094] In the inorganic filler (C) of this embodiment, not only are there two peaks in the particle size distribution within the range of 1.0 to 50.0 μm, but there may also be a third peak within that range. In that case, it is preferable that the third peak is located within the range of 20.0 to 50.0 μm. This can also be expected to have the advantage of improving thermal conductivity due to the uniform dispersion of the filler in the resin component.

[0095] In a more preferred embodiment, the resin composition of this embodiment preferably contains boron nitride and silica as the inorganic filler (C). Furthermore, in the particle size distribution of the inorganic filler containing boron nitride and silica, it is more preferable that there are at least three peaks in the particle size distribution measured by laser diffraction particle size distribution measurement method in the particle size range of 1.0 to 50.0 μm, with at least one peak in the particle size range of 1.0 to 5.0 μm, at least one peak in the particle size range of 5.0 to 20.0 μm, and at least one peak in the particle size range of 20.0 to 50.0 μm. In this case, the particle size distribution of the inorganic filler of this embodiment will have at least three peaks, but it is preferable to adjust the particle size distribution by including boron nitride and silica having at least two different particle sizes. With such a configuration, it is thought that there are further advantages such as improved thermal conductivity due to the uniform dispersion of a highly thermally conductive filler in the resin component.

[0096] (Phosphorus compound (D)) The phosphorus compound (D) of this embodiment contains a miscible phosphorus compound (D-1) that is miscible with the mixture of the polyphenylene ether compound (A) and the curing agent (B), and an inmiscible phosphorus compound (D-2) that is miscible with the mixture.

[0097] The compatible phosphorus compound (D-1) is not particularly limited as long as it acts as a flame retardant and is compatible with the mixture. Here, compatibility means that it is finely dispersed, for example at the molecular level, in the mixture of the polyphenylene ether compound (A) and the curing agent (B).

[0098] Specific examples of compatible phosphorus compounds (D-1) include phosphate ester compounds, phosphazene compounds, phosphite ester compounds, and phosphine compounds, which are phosphorus-containing compounds that do not form salts.

[0099] Examples of phosphazene compounds include cyclic or linear phosphazene compounds. Cyclic phosphazene compounds, also known as cyclophosphazenes, are compounds having a double bond in their molecule with phosphorus and nitrogen as constituent elements, and possessing a cyclic structure. Examples of phosphate ester compounds include triphenyl phosphate, tricresyl phosphate, xylenyl diphenyl phosphate, cresyl diphenyl phosphate, 1,3-phenylenebis(di2,6-xylenyl phosphate), 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide (DOPO), condensed phosphate ester compounds such as aromatic condensed phosphate ester compounds, and cyclic phosphate ester compounds. Examples of phosphite ester compounds include trimethyl phosphite and triethyl phosphite. Examples of phosphine compounds include tris-(4-methoxyphenyl)phosphine and triphenylphosphine. Furthermore, the compatible phosphorus compound may be used individually or in combination of two or more types.

[0100] The incompatible phosphorus compound (D-2) is not particularly limited as long as it acts as a flame retardant and is an incompatible phosphorus compound that does not mix with the mixture. Here, incompatible means that it does not mix with the mixture of the polyphenylene ether compound (A) and the curing agent (B), and the substance (phosphorus compound) is dispersed in the mixture in an island-like manner. When the incompatible phosphorus compound (D-2) is dispersed in the mixture in an island-like manner, the particle size of the island-like phosphorus compound is not particularly limited, but is preferably an average particle size of 0.1 μm to 100 μm, more preferably an average particle size of 0.1 μm to 70 μm, and even more preferably an average particle size of 0.1 μm to 40 μm.

[0101] Specific examples of incompatible phosphorus compounds (D-2) include phosphinate compounds, polyphosphate compounds, and phosphonium salt compounds, which are compounds containing phosphorus and forming salts, as well as phosphine oxide compounds.

[0102] Examples of phosphinate compounds include aluminum dialkylphosphinate, aluminum trisdiethylphosphinate, aluminum trismethylethylphosphinate, aluminum trisdiphenylphosphinate, zinc bisdiethylphosphinate, zinc bismethylethylphosphinate, zinc bisdiphenylphosphinate, titanyl bisdiethylphosphinate, titanyl bismethylethylphosphinate, and titanyl bisdiphenylphosphinate. Examples of polyphosphate compounds include melamine polyphosphate, melam polyphosphate, and melem polyphosphate. Examples of phosphonium salt compounds include tetraphenylphosphonium tetraphenylborate and tetraphenylphosphonium bromide. Examples of phosphine oxide compounds include phosphine oxide compounds having two or more diphenylphosphine oxide groups in the molecule (diphenylphosphine oxide compounds), more specifically, paraxylylene bisdiphenylphosphine oxide. The incompatible phosphorus compounds may be used individually or in combination of two or more.

[0103] The content ratio of the miscible phosphorus compound (D-1) to the miscible phosphorus compound (D-2) is preferably 1:2 to 2:1 by mass, and more preferably 1:1 to 3:2. With such a content ratio, it is believed that the cured product will have a high Tg and a resin composition with superior flame retardancy.

[0104] The resin composition according to this embodiment may contain only a phosphorus compound (D) consisting of the miscible phosphorus compound (D-1) and the miscible phosphorus compound (D-2) as a flame retardant, or it may also contain other flame retardants. As such a flame retardant, it may contain flame retardants other than the miscible phosphorus compound (D-1) and the miscible phosphorus compound (D-2), but from the viewpoint of halogen-free, it is preferable not to contain halogen-based flame retardants.

[0105] (Content of each component) In the resin composition of this embodiment, the content of the polyphenylene ether compound (A) is, before The amount of polyphenylene ether compound (A) is preferably 15 to 40 parts by mass, more preferably 15 to 30 parts by mass, and even more preferably 15 to 25 parts by mass, per 100 parts by mass of the total of the polyphenylene ether compound (A), the curing agent (B), and the inorganic filler (C). If the content of the polyphenylene ether compound (A) is within the above range, it is considered that a resin composition with low dielectric properties and high heat resistance can be obtained more reliably.

[0106] Furthermore, the content of the curing agent (B) is preferably 5 to 20 parts by mass, more preferably 6 to 18 parts by mass, and even more preferably 7 to 16 parts by mass, based on 100 parts by mass of the total of the polyphenylene ether compound (A), the curing agent (B), and the inorganic filler (C). If the content of the curing agent (B) is within the above range, the resin composition will have superior heat resistance of the cured product. This is thought to be because the curing reaction between the resin components of this embodiment and the curing agent proceeds favorably.

[0107] The content of the inorganic filler (C) in the resin composition of this embodiment is preferably 40 to 80 parts by mass, more preferably 50 to 80 parts by mass, and even more preferably 60 to 80 parts by mass, based on 100 parts by mass of the total of the polyphenylene ether compound (A), the curing agent (B), and the inorganic filler (C). It is believed that a cured product with high thermal conductivity can be more reliably obtained if the content of the inorganic filler (C) is within the above range.

[0108] Furthermore, the content of boron nitride in the resin composition of this embodiment is preferably 15 to 50 parts by mass, and more preferably 20 to 50 parts by mass, based on 100 parts by mass of the total of the polyphenylene ether compound (A), the curing agent (B), and the inorganic filler (C). This is thought to make it possible to more reliably obtain high thermal conductivity.

[0109] Furthermore, in the resin composition of this embodiment, the content of the phosphorus compound (D) is preferably 2 to 15 parts by mass, more preferably 2 to 12 parts by mass, and even more preferably 2 to 10 parts by mass, based on 100 parts by mass of the total of the polyphenylene ether compound (A), the curing agent (B), and the inorganic filler (C).

[0110] In the resin composition of this embodiment, the content of the compatible phosphorus compound (D-1) is preferably 2 to 15 parts by mass, and more preferably 2 to 12 parts by mass, based on 100 parts by mass of the total of the polyphenylene ether compound (A), the curing agent (B), and the inorganic filler (C). Furthermore, the content of the incompatible phosphorus compound (D-2) is preferably 5 to 25 parts by mass, and more preferably 5 to 22 parts by mass, based on 100 parts by mass of the total of the polyphenylene ether compound (A), the curing agent (B), and the inorganic filler (C). Moreover, in the resin composition, the content of the compatible phosphorus compound (D-1) is preferably 25 to 65 parts by mass, and more preferably 40 to 60 parts by mass, based on 100 parts by mass of the total of the compatible phosphorus compound (D-1) and the compatible phosphorus compound (D-2).

[0111] If the content of the aforementioned compatible phosphorus compound (D-1) and the aforementioned incompatible phosphorus compound (D-2) is within the aforementioned range, it is considered that there is an advantage in being able to achieve both flame retardancy and a high Tg.

[0112] (Other ingredients) The resin composition according to this embodiment may contain components other than those described above (other components) as necessary, as long as they do not impair the effects of the present invention. Other components contained in the resin composition according to this embodiment may further include, for example, styrene polymers, free radical compounds, reaction initiators, silane coupling agents, defoamers, antioxidants, heat stabilizers, antistatic agents, ultraviolet absorbers, dyes and pigments, dispersants and lubricants, and other additives. In addition, the resin composition of this embodiment may contain thermosetting resins such as epoxy resins, maleimide resins, aromatic hydrocarbon resins and aliphatic hydrocarbon resins, in addition to the polyphenylene ether compound (A) and the curing agent (B).

[0113] • Styrene polymers The resin composition of this embodiment may also contain a styrene polymer in addition to the components described above. Including a styrene polymer is thought to offer advantages such as further reducing the dielectric constant of the resin.

[0114] The styrene-based polymer used in this embodiment is, for example, a polymer obtained by polymerizing monomers containing styrene-based monomers, and may also be a styrene-based copolymer. Examples of the styrene-based copolymer include copolymers obtained by copolymerizing one or more styrene-based monomers with one or more other monomers copolymerizable with styrene-based monomers. Examples of the styrene-based monomers include styrene, styrene derivatives, and styrene in which some of the hydrogen atoms are substituted with substituents.

[0115] Specific styrene-based polymers can be broadly used from those already known, and are not particularly limited. Examples include polymers having a structural unit (a structure derived from a styrene monomer) represented by the following formula (3) in their molecule.

[0116] [ka]

[0117] In formula (3), R 35~R 37 Each independently represents a hydrogen atom or an alkyl group, R 38 The group is selected from the group consisting of a hydrogen atom, an alkyl group, an alkenyl group, and an isopropenyl group. The alkyl group is not particularly limited, but for example, an alkyl group having 1 to 18 carbon atoms is preferred, and an alkyl group having 1 to 10 carbon atoms is more preferred. The alkenyl group is preferably an alkenyl group having 1 to 10 carbon atoms. Specifically, examples include a methyl group, an ethyl group, a propyl group, a hexyl group, and a decyl group.

[0118] The styrene-based polymer of this embodiment preferably contains at least one structural unit represented by formula (3) above, but may also contain a combination of two or more different types. Furthermore, it is preferable that it contains a structure in which the structural unit represented by formula (3) above is repeated.

[0119] Preferred examples of styrene polymers include polymers or copolymers obtained by polymerizing or copolymerizing one or more styrene monomers such as styrene, vinyltoluene, α-methylstyrene, isopropenyltoluene, divinylbenzene, and allylstyrene. More specifically, examples include styrene-butadiene copolymers and styrene-isobutylene copolymers. Hydrogenated styrene polymers are also acceptable, such as hydrogenated methylstyrene (ethylene / butylene)methylstyrene copolymer, hydrogenated methylstyrene (ethylene-ethylene / propylene)methylstyrene copolymer, hydrogenated styrene-isoprene copolymer, hydrogenated styrene-isoprene styrene copolymer, hydrogenated styrene (ethylene / butylene) styrene copolymer, and hydrogenated styrene (ethylene-ethylene / propylene) styrene copolymer.

[0120] The styrene-based polymer may be one of the examples given above, or two or more may be used in combination.

[0121] By including such a styrene-based polymer, in addition to the effects described above, it is also possible to achieve the further effect of suppressing the moisture absorption rate in the cured product of the resin composition and preventing deterioration of electrical properties due to increased moisture absorption.

[0122] In the styrene-based polymer of the preferred embodiment, if it contains at least one structural unit represented by formula (3), the mole fraction of the structural unit is preferably about 10 to 70% of the total polymer, and more preferably 15 to 65%. This has the further advantage of maintaining compatibility with the resin, thereby ensuring uniformity of properties within the resin composition.

[0123] The polymerization form of the styrene-based polymer is not particularly limited and may be a block copolymer, alternating copolymer, random copolymer, graft copolymer, etc. It may also be in the form of an elastomer.

[0124] The weight-average molecular weight of the styrene polymer in this embodiment is preferably about 10,000 to 200,000, and more preferably about 20,000 to 150,000. A weight-average molecular weight within this range has the advantage of ensuring proper resin fluidity in the B stage of the cured resin. Here, the number-average molecular weight can be any value measured by a general molecular weight measurement method, specifically, values ​​measured using gel permeation chromatography.

[0125] In a preferred embodiment, the styrene polymer more preferably includes a styrene-isobutylene-styrene block copolymer (SIBS) containing a structural unit represented by the following formula (16). This makes it possible to obtain a resin composition with high gas barrier properties and has the advantage of suppressing moisture absorption into the resin composition.

[0126] [ka]

[0127] In equation (16), the sum of a1 and a2 represents an integer between 1,000 and 60,000, b represents an integer between 1,000 and 70,000, and the sum of a1, a2, and b represents an integer between 10,000 and 130,000.

[0128] The method for producing the styrene polymer used in this embodiment is not particularly limited, but for example, one example of a method for producing the SIBS is to first polymerize isobutylene by living cation polymerization, and then subsequently add styrene and polymerize it.

[0129] The styrene-based polymer used in this embodiment can also be a commercially available product, such as "SIBSTAR(registered trademark) 073T", "SIBSTAR(registered trademark) 103T", and "SIBSTAR(registered trademark) 102T" from Kaneka Corporation, and "Septon V9827" from Kuraray Co., Ltd.

[0130] When the resin composition of this embodiment contains the styrene polymer, the amount of the styrene polymer is preferably 1 to 6 parts by mass, and more preferably 1 to 4 parts by mass, based on 100 parts by mass of the total of the polyphenylene ether compound (A), the curing agent (B), and the inorganic filler (C).

[0131] • Free radical compounds The resin composition of this embodiment may also contain a free radical compound. The inclusion of a free radical compound is thought to offer advantages such as improved resin flowability and moldability. The free radical compound is not particularly limited, as long as it is a free radical compound used as a polymerization inhibitor.

[0132] More specific free radical compounds that are preferably used in this embodiment include: 4-amino-2,2,6,6-tetramethylpiperidine 1-oxyl free radical, 4-acetamido-2,2,6,6-tetramethylpiperidine 1-oxyl free radical, 4-amino-2,2,6,6-tetramethylpiperidine 1-oxyl free radical, 4-carboxy-2,2,6,6-tetramethylpiperidine 1-oxyl free radical, 4-cyano-2,2,6,6-tetramethylpiperidine 1-oxyl free radical, 4-glycidyloxy-2,2,6,6-tetramethylpiperidine 1-oxyl free radical, 4-hydroxy-2,2,6,6-tetramethylpiperidine 1-oxyl free radical, 4-hydroxy-2,2,6,6-tetramethylpiperidine 1-oxyl benzoate free radical, and 4-isothiocyanato-2,2,6,6-tetramethylpiperidine 1-oxyl Free radical, 4-(2-iodoacetamide)-2,2,6,6-tetramethylpiperidine 1-oxyl Free radical, 4-[2-[2-(4-iodophenoxy)ethoxy]carbonyl]benzoyloxy-2,2,6,6-tetramethylpiperidine-1-oxyl, 4-methoxy-2,2,6,6-tetramethylpiperidine 1-oxyl Free radical, 4-methacryloyloxy-2,2,6,6-tetramethylpiperidine 1-oxyl Free radical, 4-oxo-2,2,6,6-tetramethylpiperidine 1-oxyl Free radical, 4-oxo-2,2,6,6-tetramethylpiperidine 1-oxyl Free radical, 2,2,6,6-tetramethylpiperidine 1-oxyl Free radical, 2,2,6,6-tetramethyl-4-(2-propynyloxy)piperidine 1-oxyl Free radical, 2,2,6,6-tetramethylpiperidine 1-oxyl Free radical, 4,5-dihydro-4,4,5,5-tetramethyl-2-phenyl-1H-imidazole-1-yloxy-1-oxide, bis(2,2,6,6-tetramethyl-4-piperidyl-1-oxyl) sebacate, 3-carboxy-2,2,5,5-tetramethylpyrrolidine 1-oxyl Free radical, 4-(2-chloroacetamide)-2,2,6,Examples include 6-tetramethylpiperidine 1-oxyl free radical, 2-(4-nitrophenyl)-4,4,5,5-tetramethylimidazoline-3-oxide-1-oxyl free radical, 2-(14-carboxytetradecyl)-2-ethyl-4,4-dimethyl-3-oxazolidinyloxy free radical, and 1,1-diphenyl-2-picrylhydrazyl free radical. These can be used individually or in combination of two or more. The free radical compounds described above can also be commercially available, for example, from Tokyo Chemical Industry Co., Ltd.

[0133] When the resin composition of this embodiment contains the free radical compound, the content of the free radical compound is preferably 0.005 to 0.05 parts by mass, and more preferably 0.005 to 0.03 parts by mass, based on 100 parts by mass of the total of the polyphenylene ether compound (A), the curing agent (B), and the inorganic filler (C).

[0134] • Reaction initiator As described above, the resin composition according to this embodiment may contain a reaction initiator. Even if the resin composition contains the polyphenylene ether compound (A) and the curing agent (B), the curing reaction can still proceed. However, depending on the process conditions, it may be difficult to raise the temperature high enough for curing to proceed, so a reaction initiator may be added.

[0135] The reaction initiator is not particularly limited as long as it can promote the curing reaction of the resin composition. Specifically, examples include metal oxides, azo compounds, organic peroxides, and the like.

[0136] Examples of metal oxides include metal carboxylate salts.

[0137] Examples of organic peroxides include α,α'-di(t-butylperoxy)diisopropylbenzene, 2,5-dimethyl-2,5-di(t-butylperoxy)-3-hexine, benzoyl peroxide, 3,3',5,5'-tetramethyl-1,4-diphenoquinone, chloranil, 2,4,6-tri-t-butylphenoxyl, t-butylperoxyisopropyl monocarbonate, and azobisisobutyronitrile.

[0138] Examples of azo compounds include 2,2'-azobis(2,4,4-trimethylpentane), 2,2'-azobis(N-butyl-2-methylpropionamide), and 2,2'-azobis(2-methylbutyronitrile).

[0139] Among the preferred reaction initiators are 2,2'-azobis(2,4,4-trimethylpentane) and 2,2'-azobis(N-butyl-2-methylpropionamide). These reaction initiators have little effect on dielectric properties. Furthermore, because the reaction initiation temperature is relatively high, it is possible to suppress the acceleration of the curing reaction at times when curing is not required, such as during prepreg drying, and thus has the advantage of suppressing a decrease in the shelf life of the resin composition.

[0140] The reaction initiators described above may be used individually or in combination of two or more.

[0141] When the resin composition of this embodiment contains the reaction initiator, the amount is not particularly limited, but is preferably 0.1 to 0.5 parts by mass, and more preferably 0.2 to 0.4 parts by mass, based on 100 parts by mass of the total of the polyphenylene ether compound (A), the curing agent (B), and the inorganic filler (C).

[0142] (Manufacturing method) The method for producing the resin composition is not particularly limited, and examples include mixing the polyphenylene ether compound (A), the curing agent (B), the phosphorus compound (D), and other organic components as needed, and then adding an inorganic filler (C). Specifically, when obtaining a varnish-like composition containing an organic solvent, the method described in the prepreg section below can be used.

[0143] Furthermore, by using the resin composition according to this embodiment, prepregs, metal-clad laminates, wiring boards, resin-coated metal foils, and resin-coated films can be obtained as follows.

[0144] Preferably, the cured product of the resin composition has a thermal conductivity of 1.0 W / m·K or higher, and a relative permittivity of 4.0 or lower at a frequency of 10 GHz. By using the resin composition of this embodiment, it is possible to achieve both high thermal conductivity and low dielectric properties in the cured product, as well as excellent flame retardancy.

[0145] [Prepreg] Figure 1 is a schematic cross-sectional view showing an example of a prepreg 1 according to an embodiment of the present invention. In the following description, each reference numeral in the drawing refers to, respectively, 1 prepreg, 2 resin composition or semi-cured resin composition, 3 fibrous substrate, 11 metal-clad laminate, 12 insulating layer, 13 metal foil, 14 wiring, 21 wiring board, 31 resin-coated metal foil, 32, 42 resin layer, 41 resin-coated film, and 43 support film.

[0146] As shown in Figure 1, the prepreg 1 according to this embodiment comprises the resin composition or a semi-cured product 2 of the resin composition and a fibrous base material 3. This prepreg 1 comprises the resin composition or a semi-cured product 2 of the resin composition and a fibrous base material 3 present in the resin composition or the semi-cured product 2 of the resin composition.

[0147] In this embodiment, a semi-cured product refers to a resin composition that has been partially cured to the extent that it can be further cured. In other words, a semi-cured product is a resin composition that has been partially cured (stage B). For example, when a resin composition is heated, its viscosity gradually decreases at first, then curing begins, then curing begins again, and the viscosity gradually increases. In such a case, a semi-cured product would be the state between when the viscosity begins to increase and when it is not yet completely cured.

[0148] Furthermore, the prepreg obtained using the resin composition according to this embodiment may include a semi-cured product of the resin composition as described above, or it may include the uncured resin composition itself. That is, it may be a prepreg comprising a semi-cured product of the resin composition (the resin composition in stage B) and a fibrous substrate, or it may be a prepreg comprising the uncured resin composition (the resin composition in stage A) and a fibrous substrate. Also, the resin composition or the semi-cured product of the resin composition may be the resin composition that has been dried or heat-dried.

[0149] When manufacturing prepregs, the resin composition 2 is often prepared in a varnish-like form for impregnation into the fibrous substrate 3, which is the base material for forming the prepreg. In other words, the resin composition 2 is usually a resin varnish prepared in a varnish-like form. Such a varnish-like resin composition (resin varnish) is prepared, for example, as follows.

[0150] First, each component of the resin composition that is soluble in an organic solvent is added to the organic solvent and dissolved. Heating may be used as needed during this process. Then, components that are not soluble in the organic solvent (e.g., inorganic fillers) are added as needed, and the mixture is dispersed using a ball mill, bead mill, planetary mixer, roll mill, etc., until a predetermined dispersion state is reached, thereby preparing a varnish-like resin composition. The organic solvent used here is not particularly limited as long as it dissolves the modified polyphenylene ether compound and the curing agent, etc., and does not inhibit the curing reaction. Specifically, examples include toluene and methyl ethyl ketone (MEK).

[0151] The method for manufacturing the prepreg is not particularly limited as long as it can produce the prepreg. Specifically, when manufacturing the prepreg, the resin composition used in this embodiment is often prepared in a varnish-like state and used as a resin varnish, as described above.

[0152] Examples of the fibrous base material include glass cloth, aramid cloth, polyester cloth, glass nonwoven fabric, aramid nonwoven fabric, polyester nonwoven fabric, pulp paper, and linter paper. When glass cloth is used, a laminate with excellent mechanical strength can be obtained, and flattened glass cloth is particularly preferred. Specific flattening methods include, for example, continuously pressing the glass cloth with a press roll at an appropriate pressure to flatten the yarn. The thickness of the fibrous base material commonly used is, for example, 0.01 mm or more and 0.3 mm or less.

[0153] The method for manufacturing the prepreg is not particularly limited as long as it can produce the prepreg. Specifically, when manufacturing the prepreg, the resin composition according to this embodiment is often prepared in a varnish-like state as described above and used as a resin varnish.

[0154] One method for manufacturing the prepreg 1 is to impregnate a fibrous substrate 3 with a resin composition 2, for example, a resin composition 2 prepared in the form of a varnish, and then dry it. The resin composition 2 is impregnated into the fibrous substrate 3 by immersion, coating, etc. It is also possible to repeat the impregnation process multiple times as needed. Furthermore, by repeating the impregnation process using multiple resin compositions with different compositions and concentrations, it is possible to adjust the final composition and amount of impregnation to the desired level.

[0155] The fibrous substrate 3 impregnated with the resin composition (resin varnish) 2 is heated under desired heating conditions, for example, at 80°C to 180°C for 1 minute to 10 minutes. Heating yields a prepreg 1 in either a pre-cured state (Stage A) or a semi-cured state (Stage B). Heating can also cause organic solvents to volatilize from the resin varnish, reducing or removing them.

[0156] The resin composition according to this embodiment, or the prepreg comprising a semi-cured product of this resin composition, is a prepreg that preferably yields a cured product with low dielectric properties, high thermal conductivity and Tg, and excellent adhesion and flame retardancy.

[0157] [Metal-clad laminate] Figure 2 is a schematic cross-sectional view showing an example of a metal-clad laminate 11 according to an embodiment of the present invention.

[0158] As shown in Figure 2, the metal-clad laminate 11 is composed of an insulating layer 12 containing a cured product of the prepreg 1 shown in Figure 1, and a metal foil 13 laminated together with the insulating layer 12. That is, the metal-clad laminate 11 has an insulating layer 12 containing a cured product of a resin composition, and a metal foil 13 provided on top of the insulating layer 12. The insulating layer 12 may be made of the cured product of the resin composition, or it may be made of the cured product of the prepreg. The thickness of the metal foil 13 is not particularly limited and varies depending on the performance required of the final printed circuit board. The thickness of the metal foil 13 can be set appropriately according to the desired purpose, and is preferably, for example, 0.2 to 70 μm. Examples of the metal foil 13 include copper foil and aluminum foil, and if the metal foil is thin, it may be a carrier-equipped copper foil with a release layer and carrier to improve handling.

[0159] The method for manufacturing the metal-clad laminate 11 is not particularly limited as long as it can be used to manufacture the metal-clad laminate 11. Specifically, one method is to manufacture the metal-clad laminate 11 using a prepreg 1. This method involves stacking one or more prepregs 1, then stacking metal foil 13 such as copper foil on both the top and bottom surfaces or one or both surfaces, and then heat-pressure molding the metal foil 13 and prepreg 1 to laminate and integrate them, thereby producing a laminate 11 with metal foil on both sides or one side. In other words, the metal-clad laminate 11 is obtained by laminating metal foil 13 onto the prepreg 1 and then heat-pressure molding it. The heat-pressure conditions can be appropriately set depending on the thickness of the metal-clad laminate 11 to be manufactured and the type of composition of the prepreg 1. For example, the temperature can be 170-210°C, the pressure 3-4 MPa, and the time 60-150 minutes. The metal-clad laminate may also be manufactured without using a prepreg. For example, one method involves applying a varnish-like resin composition onto a metal foil to form a layer containing the resin composition on the metal foil, and then heating and pressurizing it.

[0160] The metal-clad laminate comprising an insulating layer containing a cured resin composition according to this embodiment is a metal-clad laminate having an insulating layer with low dielectric properties, high thermal conductivity and Tg, and excellent adhesion to metal foil and flame retardancy.

[0161] [Wiring board] Figure 3 is a schematic cross-sectional view showing an example of a wiring board 21 according to an embodiment of the present invention.

[0162] As shown in Figure 3, the wiring board 21 according to this embodiment is composed of an insulating layer 12 made by curing the prepreg 1 shown in Figure 1, and wiring 14 laminated together with the insulating layer 12 and formed by partially removing the metal foil 13. That is, the wiring board 21 has an insulating layer 12 containing a cured resin composition and wiring 14 provided on the insulating layer 12. The insulating layer 12 may be made of the cured resin composition or of the cured prepreg.

[0163] The method for manufacturing the wiring board 21 is not particularly limited as long as it can be manufactured. Specifically, a method for manufacturing the wiring board 21 using the prepreg 1 can be used. For example, this method involves etching the metal foil 13 on the surface of the metal-clad laminate 11 manufactured as described above to form wiring, thereby manufacturing a wiring board 21 in which wiring is provided as a circuit on the surface of the insulating layer 12. That is, the wiring board 21 is obtained by partially removing the metal foil 13 on the surface of the metal-clad laminate 11 to form a circuit. In addition to the above method, other methods for circuit formation include, for example, circuit formation by the semi-additive process (SAP) or the modified semi-additive process (MSAP). The wiring board 21 has an insulating layer 12 that has low dielectric properties, high heat resistance, and can suitably maintain low dielectric properties even after water absorption treatment.

[0164] Such a wiring board is equipped with an insulating layer that has low dielectric properties, high thermal conductivity and Tg, and excellent adhesion to metal foil and flame retardancy.

[0165] [Metal foil with resin coating] Figure 4 is a schematic cross-sectional view showing an example of a resin-coated metal foil 31 according to this embodiment.

[0166] As shown in Figure 4, the resin-coated metal foil 31 according to this embodiment comprises a resin layer 32 containing the resin composition or a semi-cured product of the resin composition, and a metal foil 13. This resin-coated metal foil 31 has the metal foil 13 on the surface of the resin layer 32. That is, this resin-coated metal foil 31 comprises the resin layer 32 and the metal foil 13 laminated together with the resin layer 32. In addition, the resin-coated metal foil 31 may have other layers between the resin layer 32 and the metal foil 13.

[0167] Furthermore, the resin layer 32 may contain a semi-cured product of the resin composition as described above, or it may contain the uncured resin composition. That is, the resin-coated metal foil 31 may comprise a resin layer containing a semi-cured product of the resin composition (the resin composition in stage B) and a metal foil, or it may comprise a resin layer containing the uncured resin composition (the resin composition in stage A) and a metal foil. Furthermore, the resin layer may contain the resin composition or a semi-cured product of the resin composition, and may or may not contain a fibrous substrate. Furthermore, the resin composition or the semi-cured product of the resin composition may be the resin composition that has been dried or heat-dried. Furthermore, the fibrous substrate may be the same as the fibrous substrate of the prepreg.

[0168] Furthermore, any metal foil used in metal-clad laminates can be used without limitation. Examples of metal foils include copper foil and aluminum foil.

[0169] The resin-coated metal foil 31 and the resin-coated film 41 may be provided with a cover film or the like, if necessary. Providing a cover film can prevent the incorporation of foreign matter. The cover film is not particularly limited, but examples include polyolefin film, polyester film, polymethylpentene film, and films formed by providing a release agent layer on these films.

[0170] The method for producing the resin-coated metal foil 31 is not particularly limited as long as it can produce the resin-coated metal foil 31. Examples of methods for producing the resin-coated metal foil 31 include applying the varnish-like resin composition (resin varnish) onto the metal foil 13 and heating it. The varnish-like resin composition is applied onto the metal foil 13, for example, by using a bar coater. The applied resin composition is heated, for example, at a temperature of 80°C to 180°C for 1 minute to 10 minutes. The heated resin composition is formed on the metal foil 13 as an uncured resin layer 32. The heating can cause the organic solvent to volatilize from the resin varnish, thereby reducing or removing the organic solvent.

[0171] The resin-coated metal foil comprising a resin layer containing the resin composition or a semi-cured product of this resin composition according to this embodiment is a resin-coated metal foil that preferably yields a cured product with low dielectric properties, high thermal conductivity and Tg, and excellent adhesion to the metal foil and flame retardancy.

[0172] [Resin-coated film] Figure 5 is a schematic cross-sectional view showing an example of a resin-coated film 41 according to this embodiment.

[0173] As shown in Figure 5, the resin-coated film 41 according to this embodiment comprises a resin layer 42 containing the resin composition or a semi-cured product of the resin composition, and a support film 43. This resin-coated film 41 comprises the resin layer 42 and a support film 43 laminated together with the resin layer 42. The resin-coated film 41 may also have other layers between the resin layer 42 and the support film 43.

[0174] Furthermore, the resin layer 42 may contain a semi-cured product of the resin composition as described above, or it may contain the uncured resin composition. That is, the resin-coated film 41 may comprise a resin layer containing a semi-cured product of the resin composition (the resin composition of stage B) and a support film, or it may comprise a resin layer containing the uncured resin composition (the resin composition of stage A) and a support film. Furthermore, the resin layer may contain the resin composition or a semi-cured product of the resin composition, and may or may not contain a fibrous substrate. Furthermore, the resin composition or the semi-cured product of the resin composition may be the resin composition that has been dried or heat-dried. Furthermore, the fibrous substrate may be the same as the fibrous substrate of the prepreg.

[0175] Furthermore, the support film 43 can be any support film used for resin-coated films without limitation. Examples of such support films include polyester film, polyethylene terephthalate (PET) film, polyimide film, polyparabanic acid film, polyether ether ketone film, polyphenylene sulfide film, polyamide film, polycarbonate film, and electrically insulating films such as polyarylate film.

[0176] The resin-coated film 41 may be provided with a cover film or the like, if necessary. Providing a cover film can prevent the incorporation of foreign matter. The cover film is not particularly limited, but examples include polyolefin film, polyester film, and polymethylpentene film.

[0177] The support film and cover film may be subjected to surface treatments such as matte treatment, corona treatment, release treatment, and roughening treatment, as needed.

[0178] The method for manufacturing the resin-coated film 41 is not particularly limited as long as it can be used to manufacture the resin-coated film 41. Examples of methods for manufacturing the resin-coated film 41 include applying the varnish-like resin composition (resin varnish) onto a support film 43 and heating it. The varnish-like resin composition is applied onto the support film 43, for example, by using a bar coater. The applied resin composition is heated, for example, at a temperature of 80°C to 180°C for 1 minute to 10 minutes. The heated resin composition is formed on the support film 43 as an uncured resin layer 42. The heating can cause the organic solvent to volatilize from the resin varnish, thereby reducing or removing the organic solvent.

[0179] A resin-coated film comprising a resin layer containing the resin composition or a semi-cured product of this resin composition according to this embodiment is a resin-coated film that preferably yields a cured product with low dielectric properties, high thermal conductivity and Tg, and excellent adhesion and flame retardancy.

[0180] This specification discloses various aspects of technology as described above, but the main technologies are summarized below.

[0181] A resin composition according to a first aspect of the present invention comprises a polyphenylene ether compound (A), a curing agent (B), an inorganic filler (C) containing boron nitride, and a phosphorus compound (D), wherein the particle size distribution of the inorganic filler (C) has at least two peaks in the particle size distribution measured by laser diffraction particle size distribution measurement method in the particle size range of 1.0 to 50.0 μm, and the phosphorus compound (D) contains a compatible phosphorus compound (D-1) that is compatible with the mixture of the polyphenylene ether compound (A) and the curing agent (B), and an incompatible phosphorus compound (D-2) that is not compatible with the mixture.

[0182] The resin composition according to the second embodiment is characterized in that, in the resin composition according to the first embodiment, at least one peak in the particle size distribution exists in the range of particle size between 1.0 μm and 10.0 μm, and at least one peak exists in the range of particle size between 10.0 μm and 50.0 μm.

[0183] The third embodiment of the resin composition is the resin composition of the first or second embodiment, wherein the inorganic filler (C) has a cumulative percentage of particles in the particle size range of 0.1 to 5.0 μm of 25 to 75 volume percent and a cumulative percentage of particles in the particle size range of 5.0 to 100.0 μm of 25 to 75 volume percent with respect to 100 volume percent of the total particle size distribution.

[0184] The fourth embodiment of the resin composition is the resin composition of any of the first to third embodiments, wherein the inorganic filler (C) further comprises at least one filler selected from the group consisting of silica, anhydrous magnesium carbonate, magnesium oxide, alumina, silicon nitride, and aluminum nitride.

[0185] The fifth aspect of the resin composition is the resin composition of the fourth aspect, wherein the inorganic filler (C) contains silica filler, and in the particle size distribution of the inorganic filler (C), there are at least three peaks in the particle size distribution measured by laser diffraction particle size distribution measurement method in the particle size range of 1.0 to 50.0 μm, and at least one of these peaks is in the particle size range of 1.0 to 5.0 μm, at least one in the particle size range of 10.0 to 20.0 μm, and at least one in the particle size range of 20.0 to 50.0 μm.

[0186] The resin composition according to the sixth embodiment is the resin composition according to any of the first to fifth embodiments, wherein the content of the inorganic filler (C) is 40 to 80 parts by mass with respect to 100 parts by mass of the total of the polyphenylene ether compound (A), the curing agent (B), and the inorganic filler (C).

[0187] The resin composition according to the seventh embodiment is the resin composition according to the sixth embodiment, wherein the content of boron nitride is 15 to 50 parts by mass per 100 parts by mass of the total of the polyphenylene ether compound (A), the curing agent (B), and the inorganic filler (C). Furthermore, it is preferable that the content of boron nitride in the inorganic filler (C) is 20 to 100 parts by mass per 100 parts by mass of the inorganic filler (C).

[0188] The resin composition according to the eighth embodiment is the resin composition according to the sixth embodiment, wherein the content of inorganic fillers other than boron nitride in the inorganic filler (C) is 20 to 60 parts by mass with respect to 100 parts by mass of the total of the polyphenylene ether compound (A), the curing agent (B), and the inorganic filler (C).

[0189] The resin composition according to the ninth embodiment is the resin composition according to the first to eighth embodiments, wherein the compatible phosphorus compound (D-1) comprises at least one selected from the group consisting of phosphate ester compounds, phosphazene compounds, phosphite compounds, and phosphine compounds.

[0190] The resin composition according to the tenth embodiment is the resin composition according to the first to ninth embodiments, wherein the incompatible phosphorus compound (D-2) comprises at least one selected from the group consisting of phosphinate compounds, polyphosphate compounds, phosphonium salt compounds, and phosphine oxide compounds.

[0191] The resin composition according to the 11th embodiment is such that, in the resin compositions of the 1st to 10th embodiments, the content of the compatible phosphorus compound (D-1) is 25 to 65 parts by mass per 100 parts by mass of the total of the compatible phosphorus compound (D-1) and the compatible phosphorus compound (D-2).

[0192] The resin composition according to the twelfth embodiment is the resin composition according to the first to eleventh embodiments, wherein the polyphenylene ether compound (A) comprises a modified polyphenylene ether compound (A-1) having at least one of the groups represented by formula (1) and formula (2).

[0193] The resin composition according to the 13th embodiment is the resin composition according to the 1st to 12th embodiments, wherein the curing agent (B) comprises at least one selected from the group consisting of a polyfunctional acrylate compound having two or more acryloyl groups in the molecule, a polyfunctional methacrylate compound having two or more methacryloyl groups in the molecule, a polyfunctional vinyl compound having two or more vinyl groups in the molecule, a styrene derivative, an allyl compound having an allyl group in the molecule, a maleimide compound having a maleimide group in the molecule, an acenaphthylene compound having an acenaphthylene structure in the molecule, and an isocyanurate compound having an isocyanurate group in the molecule.

[0194] The resin composition according to the 14th embodiment further includes a styrene polymer in addition to the resin composition according to the 1st to 13th embodiments.

[0195] The resin composition according to the 15th embodiment has a thermal conductivity of 1.0 W / m·K or higher and a relative permittivity of 4.0 or lower at a frequency of 10 GHz in the cured product of the resin compositions according to the 1st to 14th embodiments.

[0196] A prepreg according to the sixteenth aspect of the present invention is characterized by comprising a resin composition according to the first to fifteenth aspects or a semi-cured product of the resin composition and a fibrous substrate.

[0197] A resin-coated film according to the 17th aspect of the present invention is characterized by comprising a resin layer containing a resin composition of the 1st to 15th aspects or a semi-cured product of the resin composition, and a support film.

[0198] A resin-coated metal foil according to the 18th aspect of the present invention is characterized by comprising a resin layer containing a resin composition according to the 1st to 15th aspects or a semi-cured product of the resin composition, and a metal foil.

[0199] A metal-clad laminate according to the 19th aspect of the present invention is characterized by comprising an insulating layer containing a cured product of a resin composition according to the 1st to 15th aspects or a cured product of a prepreg according to the 16th aspect, and a metal foil.

[0200] A wiring board according to the 20th aspect of the present invention is characterized by comprising an insulating layer containing a cured product of a resin composition according to the 1st to 15th aspects or a cured product of a prepreg according to the 16th aspect, and wiring.

[0201] The present invention will be described in more detail below with reference to examples, but the scope of the present invention is not limited thereto. [Examples]

[0202] [Examples 1-20 and Comparative Examples 1-4] In this embodiment, each component used in preparing the resin composition will be described.

[0203] (Polyphenylene ether compounds) PPE1: A polyphenylene ether compound having a methacryloyl group at the terminal end (a modified polyphenylene ether obtained by modifying the terminal hydroxyl group of polyphenylene ether with a methacryloyl group, represented by formula (15) above, where Y in formula (15) is a dimethylmethylene group (represented by formula (12), where R in formula (12) is...) 33 and R 34 A modified polyphenylene ether compound (SA9000, manufactured by SABIC Innovative Plastics, with a methyl group at the end), weight-average molecular weight Mw2000, and 2 terminal functional groups. PPE2: This is a modified polyphenylene ether obtained by reacting polyphenylene ether with chloromethylstyrene. Specifically, it is a modified polyphenylene ether obtained by the following reaction:

[0204] First, 200 g of polyphenylene ether (SA90, manufactured by SABIC Innovative Plastics, with 2 terminal hydroxyl groups and a weight-average molecular weight Mw1700), 30 g of a mixture of p-chloromethylstyrene and m-chloromethylstyrene in a mass ratio of 50:50 (chloromethylstyrene: CMS, manufactured by Tokyo Chemical Industry Co., Ltd.), 1.227 g of tetra-n-butylammonium bromide as a phase transfer catalyst, and 400 g of toluene were charged into a 1-liter three-necked flask equipped with a temperature controller, a stirrer, a cooling system, and a dropping funnel, and the mixture was stirred. The mixture was then stirred until the polyphenylene ether, chloromethylstyrene, and tetra-n-butylammonium bromide dissolved in the toluene. During this process, the mixture was gradually heated until the liquid temperature reached 75°C. Then, an aqueous sodium hydroxide solution (20 g sodium hydroxide / 20 g water) was added dropwise to the solution over 20 minutes as an alkali metal hydroxide. The mixture was then stirred at 75°C for 4 hours. Next, the contents of the flask were neutralized with 10% by mass hydrochloric acid, and then a large amount of methanol was added. This caused a precipitate to form in the liquid in the flask, that is, the products contained in the reaction mixture in the flask were re-precipitated. This precipitate was then removed by filtration, washed three times with a methanol-water mixture in a mass ratio of 80:20, and then dried under reduced pressure at 80°C for 3 hours.

[0205] The obtained solid, 1The compound was analyzed by 1H-NMR (400 MHz, CDCl3, TMS). NMR analysis revealed a peak at 5-7 ppm originating from a vinylbenzyl group (ethenylbenzyl group). This confirmed that the obtained solid is a modified polyphenylene ether compound having a vinylbenzyl group (ethenylbenzyl group) as a substituent at the molecular terminus. Specifically, it was confirmed to be an ethenylbenzyl polyphenylene ether. This obtained modified polyphenylene ether compound is represented by formula (14) above, where Y is a dimethylmethylene group (represented by formula (12), and R in formula (12)). 33 and R 34 The compound was a modified polyphenylene ether in which (the group is a methyl group), Z is a phenylene group, R1 to R3 are hydrogen atoms, and n is 1.

[0206] Furthermore, the number of terminal functional groups in the modified polyphenylene ether was measured as follows.

[0207] First, the modified polyphenylene ether was accurately weighed. Let the weight be X (mg). Then, this weighed modified polyphenylene ether was dissolved in 25 mL of methylene chloride, and 100 μL of an ethanol solution of 10% by mass of tetraethylammonium hydroxide (TEAH) (TEAH:ethanol (volume ratio) = 15:85) was added to the solution. The absorbance (Abs) at 318 nm was then measured using a UV spectrophotometer (UV-1600, Shimadzu Corporation). From the measurement results, the number of terminal hydroxyl groups of the modified polyphenylene ether was calculated using the following formula.

[0208] Residual OH amount (μmol / g) = [(25×Abs) / (ε×OPL×X)]×10 6

[0209] Here, ε represents the extinction coefficient, which is 4700 L / mol·cm. OPL is the cell path length, which is 1 cm.

[0210] Furthermore, the calculated amount of residual OH (number of terminal hydroxyl groups) in the modified polyphenylene ether was almost zero, indicating that the hydroxyl groups of the polyphenylene ether before modification were almost completely modified. From this, it was found that the decrease from the number of terminal hydroxyl groups of the polyphenylene ether before modification corresponds to the number of terminal hydroxyl groups of the polyphenylene ether before modification. In other words, the number of terminal hydroxyl groups of the polyphenylene ether before modification corresponds to the number of terminal functional groups of the modified polyphenylene ether. That is, the number of terminal functional groups was 2.

[0211] Furthermore, the intrinsic viscosity (IV) of modified polyphenylene ether was measured in methylene chloride at 25°C. Specifically, the intrinsic viscosity (IV) of modified polyphenylene ether was measured using a viscometer (Schott AVS500 Visco System) with a 0.18 g / 45 ml solution of modified polyphenylene ether in methylene chloride (at a liquid temperature of 25°C). As a result, the intrinsic viscosity (IV) of modified polyphenylene ether was 0.086 dl / g.

[0212] Furthermore, the molecular weight distribution of the modified polyphenylene ether was measured using GPC. The weight-average molecular weight (Mw) was then calculated from the obtained molecular weight distribution. The result showed that Mw was 2300.

[0213] (Hardening agent) • Hardener 1: Triaryl isocyanurate (TAIC, manufactured by Nippon Chemical Corporation) • Hardener 2: Divinylbenzene (DVB manufactured by Nippon Steel & Sumitomo Metal Corporation)

[0214] (Inorganic fillers) • Boron Nitride 1: MARUKA Corporation's "AP-10S", volume-average particle size 3.0 μm • Boron Nitride 2: Denka Corporation's "SGP", volume-average particle size 18 μm • Silica 1: "FB-7SDC" manufactured by Denka Co., Ltd., volume average particle size 5 μm • Alumina: "DAW-03AC" manufactured by Denka Co., Ltd., volume average particle size 8 μm

[0215] (Phosphorus compound (D)) • Compatible phosphorus compound (D-1) 1: Aromatic condensed phosphate ester compound, manufactured by Daihachi Chemical Industry Co., Ltd., "PX-200", phosphorus concentration 9% by mass • Compatible phosphorus compound (D-1)2: Cyclic phosphazene compound, manufactured by Otsuka Chemical Co., Ltd., "SPB-100", phosphorus concentration 13% by mass • Incompatible phosphorus compound (D-2)1: Diphenylphosphine oxide compound, manufactured by Jin-Yi Chemical Co., Ltd., "PQ60", phosphorus concentration 12% by mass • Incompatible phosphorus compound (D-2)2: Phosphate compound, manufactured by Clariant Japan Co., Ltd., "OP-935", phosphorus concentration 23% by mass

[0216] (Reaction initiator) • Peroxide initiator: PBP (1,3-bis(butylperoxyisopropyl)benzene; Perbutyl P manufactured by NOF Corporation)

[0217] (Styrene polymer) • Styrene polymer 1: Hydrogenated methylstyrene (ethylene / butylene) methylstyrene copolymer (Septon V9827 manufactured by Kuraray Co., Ltd., weight-average molecular weight: 92000) • Styrene polymer 2: Styrene-isobutylene-styrene triblock copolymer (manufactured by Kaneka Corporation, number average molecular weight 85,000, mole fraction of styrene: 30%)

[0218] (Free radical compounds) • Free radical compound 1: 4-benzoyloxytempo, a free radical compound represented by the following formula (H0878, manufactured by Tokyo Chemical Industry Co., Ltd.)

[0219] [ka]

[0220] (Preparation method) First, each organic resin component other than the inorganic filler was added to toluene as a solvent in the compositions (parts by mass) shown in Tables 1 and 2, so that the solid content concentration was 60-70% by mass, and the mixture was stirred. The mixture was then stirred for 60 minutes. After that, each filler was added to the resulting liquid in the proportions (parts by mass) shown in Tables 1 and 2, and the inorganic filler was dispersed using a bead mill. In this way, a varnish-like resin composition (varnish) was obtained.

[0221] Next, an evaluation substrate (cured prepreg) was obtained as follows.

[0222] The obtained varnish was impregnated into a fibrous substrate (glass cloth: Asahi Kasei Corporation's #1078 type, L glass), and then heated and dried at 110°C for 3 minutes to produce a prepreg. Then, 1, 2, 4, and 6 sheets of each of the obtained prepregs were stacked, and copper foil (Furukawa Electric Co., Ltd.'s "FV-WS" copper foil, thickness: 35 μm) was bonded to both sides of each stack. The stacks were then heated to 200°C at a heating rate of 4°C / min, and then heated and pressurized at 200°C for 120 minutes under a pressure of 3 MPa to produce copper-clad laminates of three different thicknesses.

[0223] The copper-clad laminates prepared as described above were used as evaluation substrates and evaluated using the methods shown below. For the measurement of thermal conductivity described later, a single-layer cured prepreg and a copper-clad laminate with two layers of prepreg removed (cured prepreg) were used. For the evaluation test of dielectric properties (relative permittivity), a copper-clad laminate with four layers of prepreg removed (cured prepreg) was used. Furthermore, for the evaluation test of flame retardancy described later, copper-clad laminates with four layers of prepreg and six layers of prepreg removed (cured prepreg) were used. For the measurement and evaluation of g, a copper-clad laminate with four layers of prepreg removed (cured prepreg) was used.

[0224] [Dielectric properties (relative permittivity)] The relative permittivity (Dk) of the evaluation substrate (cured prepreg) at 10 GHz was measured using the cavity resonator perturbation method. Specifically, a network analyzer (N5230A manufactured by Keysight Technologies, Inc.) was used to measure the relative permittivity of the evaluation substrate at 10 GHz. The acceptance criterion in this embodiment was Dk ≤ 4.0.

[0225] [Copper foil peel strength] First, for the peel strength (copper foil peel) test, copper-clad laminates (CCLs) were prepared using the prepregs of each example and comparative example. Specifically, four prepregs were stacked, and 35 μm thick copper foil (FV-WS manufactured by Furukawa Electric Co., Ltd.) was bonded to both surfaces. Under vacuum conditions, the material was heated and pressurized at a temperature of 200°C and a pressure of 3 MPa for 120 minutes to obtain a 510 μm thick copper-clad laminate (CCL) (evaluation substrate) with copper foil bonded to both sides.

[0226] Then, using the obtained CCL, the peel strength of the copper foil from the insulating layer was measured in accordance with JIS C 6481. A pattern with a width of 10 mm and a length of 100 mm was formed and peeled off at a speed of 50 mm / min using a tensile testing machine, and the peel strength at that time was measured. The unit of measurement is N / mm. The acceptance criterion in this example was set at 0.40 N / mm or higher.

[0227] [Thermal conductivity] The thermal conductivity of the obtained evaluation substrates (cured prepregs) was measured according to the ASTM D5470 standard. Specifically, the thermal resistance and thickness of the obtained evaluation substrates (cured single prepreg and cured double prepreg) were measured using a thermal properties evaluation device (T3Ster DynTIM Tester manufactured by Mentor Graphics). The measured values ​​were plotted on a graph, approximated by a straight line, and the thermal conductivity was calculated from the increase in thermal resistance and thickness. In this embodiment, the acceptable thermal conductivity was set at 1.0 W / m·K or higher.

[0228] [Glass transition temperature (Tg)] The Tg of the prepreg was measured using a viscoelastic spectrometer "DMS100" manufactured by Seiko Instruments Inc. Dynamic viscoelasticity measurement (DMA) was performed using a bending module at a frequency of 10 Hz. Tg was defined as the temperature at which tanδ was maximized when the temperature was increased from room temperature to 280°C at a heating rate of 5°C / min. In this example, the acceptance criterion was set as Tg ≥ 150°C.

[0229] [Flame retardant] A test piece measuring 125 mm in length and 12.5 mm in width was cut from the evaluation substrate. This test piece was then subjected to a combustion test in accordance with Underwriters Laboratories' "Test for Flammability of Plastic Materials - UL 94". The evaluation criteria were as follows: ◎: When both plate thickness 0.75mmt and plate thickness 0.5mmt are V-0. ○: When the plate thickness is 0.5mmt and V-0 ×: If V-0 is not reached even with a plate thickness of 0.5mmt

[0230] [Particle size distribution and peaks of inorganic fillers] The particle size distribution of the inorganic fillers in each example and comparative example was determined by measuring with a laser diffraction / scattering particle size distribution analyzer LA-960V2 (manufactured by Horiba, Ltd.). The specifications of the analyzer are as follows. Measurement principle: Mie scattering theory Measurement method: Flow measurement Measurement range: 0.01 μm to 5000 μm Light source: LD (650nm), approximately 5mW, LED (405mm), approximately 3mW Detectors: 1 x ring-shaped 64-segment silicon photodiode, 5 x 4-channel array detectors, 3 x silicon photodetectors Refractive index: 1.460-0.000i

[0231] The specifications of the measurement unit (circulation system) are as follows: Dispersion: Ultrasonic probe Circulation: Centrifugal pump Agitation: Rotary blades Flow cell material: synthetic quartz

[0232] The particle size distribution measurement conditions are as follows.

[0233] Each measurement sample was introduced into the flow cell via the sample bath using toluene as the dispersion solvent, and laser diffraction / scattering particle size distribution measurement was performed under stirring conditions.

[0234] The particle size distribution was analyzed and calculated using the analysis software LA-960 for Windows included with the LA-960V2. The peaks in the particle size distribution were determined by calculation using the volume ratio of the measured particle size distribution.

[0235] The results of each of the above evaluations are shown in Table 1 and Table 2.

[0236] [Table 1]

[0237] [Table 2]

[0238] (Discussion) As can be seen from Table 1, it was confirmed that in all the Examples using the resin composition of the present invention, cured products with low dielectric properties, high thermal conductivity and high Tg, and excellent adhesion and flame retardancy could be obtained.

[0239] On the other hand, as shown in Table 2, in Comparative Example 1, the sample using only the compatible phosphorus compound (D-1) as the phosphorus compound (D) failed to obtain sufficient Tg and flame retardancy. Similarly, in Comparative Example 2, the sample using only the compatible phosphorus compound (D-2) failed to obtain sufficient thermal conductivity and flame retardancy. In Comparative Example 3, which used only silica and no boron nitride as the inorganic filler (C), the thermal conductivity was inferior, and in Comparative Example 4, which used only alumina, low dielectric properties could not be obtained. In other words, it was found that sufficient thermal conductivity and / or low dielectric properties cannot be obtained without using boron nitride. Furthermore, even when boron nitride was used as the inorganic filler (C) as in Comparative Example 5, if there was only one peak in the particle size distribution of the inorganic filler (C) in the range of particle size 1.0 to 50.0 μm, sufficient adhesion to the copper foil could not be obtained. Furthermore, the results from Comparative Example 6 showed that even when boron nitride is used as the inorganic filler (C), sufficient thermal conductivity cannot be obtained if there are not at least two peaks in the particle size range of 1.0 to 50.00 μm.

[0240] This application is based on Japanese Patent Application No. 2021-210991, filed on 24 December 2021, the contents of which are included in this application.

[0241] In order to express the present invention, the invention has been adequately and sufficiently described above through embodiments with reference to specific examples and drawings, etc. However, those skilled in the art should recognize that it is easy to modify and / or improve the embodiments described above. Therefore, unless the modifications or improvements implemented by those skilled in the art fall outside the scope of the claims described in the claims, such modifications or improvements shall be interpreted as being included within the scope of the claims. [Industrial applicability]

[0242] The present invention has broad industrial applicability in the technical fields of electronic materials, electronic devices, optical devices, and the like.

Claims

1. Polyphenylene ether compound (A) and Hardener (B), An inorganic filler (C) containing two or more boron nitrides of different particle sizes and silica filler, It contains phosphorus compound (D), In the particle size distribution of the inorganic filler (C), at least three peaks of the particle size distribution measured by the laser diffraction particle size distribution measurement method exist in the particle size range of 1.0 to 50.0 μm, and at least one of these peaks exists in the particle size range of 1.0 to 5.0 μm, at least one in the particle size range of 5.0 to 20.0 μm, and at least one in the particle size range of 20.0 to 50.0 μm. The phosphorus compound (D) is a resin composition containing a compatible phosphorus compound (D-1) that is compatible with the mixture of the polyphenylene ether compound (A) and the curing agent (B), and an incompatible phosphorus compound (D-2) that is not compatible with the mixture.

2. The resin composition according to claim 1, wherein the inorganic filler (C) has a cumulative percentage of particles with a particle size in the range of 0.1 to 5.0 μm of 25 to 75 volume percent and a cumulative percentage of particles with a particle size of 5.0 to 100.0 μm of 25 to 75 volume percent with respect to 100 volume percent of the overall particle size distribution.

3. The resin composition according to claim 1, wherein the inorganic filler (C) further comprises at least one filler selected from the group consisting of anhydrous magnesium carbonate, magnesium oxide, alumina, silicon nitride, and aluminum nitride.

4. The resin composition according to claim 1, wherein the amount of the inorganic filler (C) is 40 to 80 parts by mass with respect to 100 parts by mass of the total of the polyphenylene ether compound (A), the curing agent (B), and the inorganic filler (C).

5. The resin composition according to claim 4, wherein the content of boron nitride is 15 to 50 parts by mass with respect to 100 parts by mass of the total of the polyphenylene ether compound (A), the curing agent (B), and the inorganic filler (C).

6. The resin composition according to claim 4, wherein the content of inorganic fillers other than boron nitride in the inorganic filler (C) is 20 to 60 parts by mass with respect to 100 parts by mass of the total of the polyphenylene ether compound (A), the curing agent (B), and the inorganic filler (C).

7. The resin composition according to claim 1, wherein the compatible phosphorus compound (D-1) comprises at least one selected from the group consisting of phosphate ester compounds, phosphazene compounds, phosphite ester compounds, and phosphine compounds.

8. The resin composition according to claim 1, wherein the non-miscible phosphorus compound (D-2) comprises at least one selected from the group consisting of phosphinate compounds, polyphosphate compounds, phosphonium salt compounds, and phosphine oxide compounds.

9. The resin composition according to claim 1, wherein the content of the compatible phosphorus compound (D-1) is 25 to 65 parts by mass per 100 parts by mass of the total of the compatible phosphorus compound (D-1) and the compatible phosphorus compound (D-2).

10. The resin composition according to claim 1, wherein the polyphenylene ether compound (A) comprises a modified polyphenylene ether compound (A-1) having at least one of the groups represented by the following formulas (1) and (2). 【Chemistry 1】 (In formula (1), s represents an integer from 0 to 10. Z represents an arylene group. R 1 ~R 3 (Each of these independently represents a hydrogen atom or an alkyl group.) 【Chemistry 2】 (In formula (2), R 4 (This represents a hydrogen atom or an alkyl group.)

11. The resin composition according to claim 1, wherein the curing agent (B) comprises at least one selected from the group consisting of a polyfunctional acrylate compound having two or more acryloyl groups in its molecule, a polyfunctional methacrylate compound having two or more methacryloyl groups in its molecule, a polyfunctional vinyl compound having two or more vinyl groups in its molecule, a styrene derivative, an allyl compound having an allyl group in its molecule, a maleimide compound having a maleimide group in its molecule, an acenaphthylene compound having an acenaphthylene structure in its molecule, and an isocyanurate compound having an isocyanurate group in its molecule.

12. The resin composition according to claim 1, further comprising a styrene polymer.

13. The resin composition according to claim 1, wherein the cured product of the resin composition has a thermal conductivity of 1.0 W / m·K or more and a relative permittivity of 4.0 or less at a frequency of 10 GHz.

14. A prepreg comprising a resin composition according to any one of claims 1 to 13 or a semi-cured product of the resin composition, and a fibrous substrate.

15. A resin-coated film comprising a resin layer containing the resin composition according to any one of claims 1 to 13 or a semi-cured product of the resin composition, and a support film.

16. A resin-coated metal foil comprising a resin layer containing the resin composition according to any one of claims 1 to 13 or a semi-cured product of the resin composition, and a metal foil.

17. A metal-clad laminate comprising an insulating layer containing a cured resin composition according to any one of claims 1 to 13, and a metal foil.

18. A wiring board comprising an insulating layer containing a cured resin composition according to any one of claims 1 to 13, and wiring.

19. A metal-clad laminate comprising an insulating layer containing a cured prepreg according to claim 14, and a metal foil.

20. A wiring board comprising an insulating layer containing a cured prepreg according to claim 14, and wiring.

Citation Information

Patent Citations

  • Homogeneous dispersion liquid of cross-linkable hydrocarbon resin composition, prepreg prepared from homogeneous dispersion liquid, and high-thermal-conductivity thermosetting copper-clad plate

    CN112111074A

  • Aggregated boron nitride particle, composition containing aggregated boron nitride particle, and three-dimensional integrated circuit having layer comprising composition

    JP2013241321A

  • Interlaminar filler composition for stacked-type semiconductor device, stacked-type semiconductor device, and method for producing stacked-type semiconductor device

    JP2014208818A

  • PPE-containing resin composition

    JP2015067700A

  • Resin composition for dielectric and high-frequency dielectric device

    JP2015168731A